Artist’s Statement: Recognizing the Interdisciplinary Journal of Partnership Studies Taking Flight - Nesser, Stephen (Interdisciplinary Journal of Partnership Studies, 2015)
Artist’s Statement for the cover art of IJPS volume 1, issue 1: Life Partners at Twilight, 2015. Watercolor on paper.